CONSUMER COMPLAINT BEHAVIOR (CCB) PELANGGAN MINIMARKET DI JOMBANG - Rahayu Rahayu (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
The business development are getting very competitive especially in retail…….; the businessman must be responsive to the customers complaint and handle the unsatisfied service given. In this research, the categorized of cause of complaint are: the price labeling, the miscalculated by cashier, the services and products problems. Alternative of Cunsomer Complaint Behavior which is taken by the customers influenced by simple complaints and asking compensation to fix demographic factors or some situation of CCB is also influence by choosing complaints alternatives. Some alternatives action of CCB done by the customers with dissatisfactions are : complaining by phone, meeting cashiers directly  (the most popular alternative), meeting the retail employees, meeting the customer service representative, calling the retail company to obtain the procedure on how to complain, meeting the supervisor, complaining by mass media (radio, newspapers), using the mediation service by the consumers complaint service. Customers have many CCB hierarchies, however, the procedures and actions intensity are varies. The action intensity is the next step of hierarchy and the situational to the customers. The economics and psychological factor is the most basic consideration to differentiating steps of CCB which need for the customers doing complaint.